2015
DOI: 10.3109/02652048.2015.1035686
|View full text |Cite
|
Sign up to set email alerts
|

Encapsulation of orange terpenes investigating a plasticisation extrusion process

Abstract: Extrusion is widely used for flavour encapsulation. However, there is a lack of process understanding. This study is aimed at improving the understanding of a counter rotating twin screw extrusion process. Orange terpenes as model flavour, maltodextrin and sucrose as matrix materials, and a water feed rate between 4.0% and 5.7% were applied. Product temperatures < 80 °C and specific mechanical energy inputs <260 Wh/kg resulted. Amorphous and partly crystalline samples were obtained. The loss of crystalline suc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(5 citation statements)
references
References 22 publications
0
4
0
1
Order By: Relevance
“…For proteins, non-allergic plant proteins extracted from pulses, cereals, or oilseeds using eco-friendly techniques have gained attention recently [15]. Several studies have reported the use of maltodextrin to encapsulate orange turpentine, tocopherol, and ascorbic acid using extrusion [16,17]. It was also reported that starch, mannose, and cyclodextrins could be used for the same purpose.…”
Section: Introductionmentioning
confidence: 99%
“…For proteins, non-allergic plant proteins extracted from pulses, cereals, or oilseeds using eco-friendly techniques have gained attention recently [15]. Several studies have reported the use of maltodextrin to encapsulate orange turpentine, tocopherol, and ascorbic acid using extrusion [16,17]. It was also reported that starch, mannose, and cyclodextrins could be used for the same purpose.…”
Section: Introductionmentioning
confidence: 99%
“…Selanjutnya, zat terpen dari jeruk dan campuran penyalut serta air diumpankan ke dalam alat twin screw extruder. Die dengan 156 lubang berdiameter 0.9 dan pemotong (hot die face cutting) digunakan untuk mendapatkan butiran kecil dari ekstrudat silinder yang dihasilkan [14]. Teknik ekstrusi secara sederhana juga bisa dilakukan dengan bantuan syringe seperti yang dilakukan oleh Wibowo dkk.…”
Section: Pembahasan 31 Teknik Enkapsulasiunclassified
“…At temperatures ranging from 105°C to 145°C, orange turpentine was encapsulated in maltodextrin DE 17. Tocopherol was also encapsulated in maltodextrin DE 12 at the similar temperature range of 105°C-115°C (Tackenberg et al, 2015). Chang et al (2019) explored the encapsulation of ascorbic acid using a twin-screw extruder and HME technology to produce maltodextrin-gum arabic, maltodextrin and maltodextrintrehalose-based glassy extrudates comprising ascorbic acid (dispersed phase).…”
Section: Extrusion As Mode Of Encapsulationmentioning
confidence: 99%
“…At temperatures ranging from 105°C to 145°C, orange turpentine was encapsulated in maltodextrin DE 17. Tocopherol was also encapsulated in maltodextrin DE 12 at the similar temperature range of 105°C–115°C (Tackenberg et al , 2015).…”
Section: Hot-melt Extrusionmentioning
confidence: 99%